Age, Low Education and Unemployment are Associated with Intimate Partner Violence among Women - Maidarti, Mila (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objective: To describe the prevalence of violence in women visiting Puskesmas Kecamatan Makassar by their partners and their association with socio-demographic factors and gender role perception. Methods: A cross-sectional study using validated WHO questionnaires was conducted on 141 women visiting Puskesmas Makassar in December 2011 to identify presence of physical, sexual or emotional abuse and women’s perception of gender roles. The data was then analyzed using a combination of univariate analysis and Chisquare test. Results: Our study showed that the lifetime prevalence of female abuse in Puskesmas Makassar population was 21.3%, with physical violence constituting 5.7%, sexual violence 6.4% and emotional abuse 17.0% among the subjects. Violence was associated with the wife’s demographic factor (age >35 years, education 35 years and unemployment). Women’s perception of gender role was not significantly associated with prevalence of abuse Conclusion: A woman’s age and her partner’s age of more than 35 years, an education level of less than nine years, and unemployed partner, were all significantly associated with the lifetime prevalence of female abuse, and was not consistent with gender role beliefs. [Indones J Obstet Gynecol 2013; 37-2: 63-70] Keywords: gender role perception, intimate partner violence, Puskesmas Makassar